Heavy Metal Stress and Some Mechanisms of Plant Defense Response - Abolghassem Emamverdian; Yulong Ding; Farzad Mokhberdoran; Yinfeng Xie (The Scientific World Journal)
Unprecedented bioaccumulation and biomagnification of heavy metals (HMs) in the environment have become a dilemma for all living organisms including plants. HMs at toxic levels have the capability to interact with several vital cellular biomolecules such as nuclear proteins and DNA, leading to excessive augmentation of reactive oxygen species (ROS). This would inflict serious morphological, metabolic, and physiological anomalies in plants ranging from chlorosis of shoot to lipid peroxidation and protein degradation. In response, plants are equipped with a repertoire of mechanisms to counteract heavy metal (HM) toxicity. The key elements of these are chelating metals by forming phytochelatins (PCs) or metallothioneins (MTs) metal complex at the intra- and intercellular level, which is followed by the removal of HM ions from sensitive sites or vacuolar sequestration of ligand-metal complex. Nonenzymatically synthesized compounds such as proline (Pro) are able to strengthen metal-detoxification capacity of intracellular antioxidant enzymes. Another important additive component of plant defense system is symbiotic association with arbuscular mycorrhizal (AM) fungi. AM can effectively immobilize HMs and reduce their uptake by host plants via binding metal ions to hyphal cell wall and excreting several extracellular biomolecules. Additionally, AM fungi can enhance activities of antioxidant defense machinery of plants.